Pemanfaatan darah manusia yang kadaluarsa sebagai pengganti darah domba dalam pembuatan media Agar Darah Plat (ADP) - Djannatun, Titiek; T Rochani, Jekti; Wikaningrum, Riyani; Widiyanti, Dian; Rahim Pane, Abdul (Lembaga Penelitian Universitas YARSI, 2008)
The use of blood agar media to grow and to isolate the pathogenic bacteria, and to compare the hemolytic ability of the bacteria is well known. The aim of this study was to investigate the possibility of using expired human blood as substitute for the sheep blood agar media. In this study five days before expired and five days after expired human blood were washed once, twice and centrifuged. Sheep blood was used as positive control and five days after and before expired blood without treatment was used as negative control. The prepared media were used to grow six isolates wild strain bacteria (Staphylococcus aureus, Streptococcus B haemolyticus,Streptococcus y haemolyticus, Streptococcus pneumoniae, Vibrio El Tor and Clostridium perfringens). The result indicated that blood agar medium, prepared using human blood which was nearly expired or expired, have the same results in culture growth of the tested bacteria compared to the standard blood agar had media using sheep blood.